K Kajian hambatan samping terhadap kinerja ruas pada kawasan komersil (studi kasus: Jalan Boulevard kota Makassar) - Hamsir, Rafiqah; Said, Lambang Basri; Syarkawi, Mukhtar Thahir; Kasim, Muhammad Ridha (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The traffic on the Makassar City Boulevard Road segment operates using a two-way system, with a significant volume of vehicles and frequent obstacles on the sides. It arises as a result of the presence of commercial zones, encompassing trade and service establishments such as offices, banks, stores, restaurants, hotels, and shopping centers, where transactions between sellers and purchasers take place. Hence, this study was carried out to investigate the influence of side barriers obstructions on the performance of the Makassar City Boulevard Road segment utilizing the MKJI 1997 methodology. The analysis reveals that the highest frequency of side barriers on the section of Jalan Boulevard Makassar City occurs on Thursdays at point 2 (in front of Jims Honey Store), with a rate of 592 pcu/h or 4.10% of the total number of side barrier events at that location, which is 14450 pcu/h. These side barriers are classified as high class (H) and are predominantly found in commercial areas with high roadside activity. Thus, it has been demonstrated that side barriers have a notable influence on the performance of the Makassar City Boulevard Road portion, leading to a fall in speed and capacity, as well as a decline in service quality standards.